Comparative study of patients suffering sore throat after general anesthesia using laryngeal mask airway and cuffed pharyngeal tube in adults - Hassani V (Tehran University Medical Journal, 2001)
Post-operative sore throat is one of the most common complications and complaints of patients after general anesthesia especially in operations that need endotracheal intubations. Its causes are: size of endotracheal tube and type of its cuff, inadequate airway humidification, trauma during intubation and suctioning, high flow of inspiratory gases, surgical manipulation of airway and adjacent organs, ect. Use of instruments with less invasion to upper respiratory tract, for example, face mask and airway, LMA or CPT are methods, used for decreasing the rate of post-operative sore throat. This study was performed to compare the rate of sore throat after general anesthesia between Laryngeal Mask Airway (LMA) and Cuffed Pharyngeal Tube (CPT). From the patients, 120 ASA: PS-I cases, were selected, who were candidates for elective surgery of Orthopedics, Urology, General surgery and Gynecology in Hazrat Rasool-Akram Hospital Complex in the year 2000. Their operation were performed in supine position and did not need muscle relaxation and the patients had spontaneous breathing. Duration of surgery was less than 2 hours. The patients were randomly allocated into two groups: LMA was used for one group and CPT for others. Immediately after operation, in the recovery room and at 6, 12, 18 and 24 hours after removing the tube, the patients were asked about sore throat and the results were recorded in the related sheets. The results was 31.7 percent of patients in group LMA and 0 percent of patients in group CPT, had sore throat. There were significant difference between groups (LMA and CPT) in presentation of sore throat (P<0.001).